The role of multimedia in improving the achievement level A semi-experimental study on the sixth grade students in Lattakia - Ahmad , Moteah; Sultan, Manal; Shahen, Youssef (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of the research was to construct and design a science-based multimedia education program for Grade 6 students, and to investigate the impact on learning achievement in the light of Bloom’s cognitive levels (remembering, understanding, applying) and at the test level as a whole. The researcher used the semi-experimental method, where the sample was divided into two experimental groups taught by multimedia software, and a control group taught in the traditional way by the traditional school explanation. The researcher selected two samples of the sixth grade students randomly and systematically. The total number of students in each group was 25 divided by gender (23 males and 12 females) for each group, bringing the total number of students to 50. The first module of the science curriculum for the sixth grade was selected, entitled (Classification of Biology and Study of Inter-Biology Relationships in the Environment), Chapter 1 (General Characteristics and Classification of Biology) for the first semester of the academic year 2017-2018. Using the appropriate statistical methods, an impact of the multimedia learning program was found in the post-post and post-post-test trials for the experimental group.